“Natura 2000” ecological network in the aspect of sustainable development - Łaska, Grażyna (Ecological Questions, 2013)
The work discusses the operation of the “Natura 2000” European Ecological Network in aspects related to sustainable development, i.e. taking into account economic undertakings and planned business projects which conform to the idea of sound management of natural resources. The legal basis for the Natura 2000 network is the Habitats Directive 92/43/EEC and the Birds Directive 79/409/EEC, which have been transposed into the Polish law, especially in the Act of 16 April 2004 on the protection of nature. Both environmental conservation directives seek to establish an ecological network of protected areas (so-called Natura 2000 sites) across Europe. In Poland, Natura 2000 comprises Special Protection Areas for birds (SPAs, or bird sites), Special Areas of Conservation (SACs, or habitat sites) and Sites of Community Importance (SCIs) (based on the Act on the protection of nature). Studies have demonstrated that Poland currently has a total of 141 SPAs with an area of 55,228 km2, which makes up 15.6% of Poland’s land area, and 364 SACs occupying 2.89 million ha, which represents 8.95% of the total area of Poland. The Natura 2000 European Ecological Network Programme supports the principle of sustainable development in the context of guidelines set out in Art. 6 (3) and (4) of the Habitats Directive (92/42/EEC) under which any plan or project which is likely to have a significant impact on a Natura 2000 site should be subject to appropriate assessment to determine how it affects the site. Environmental impact assessment is a preventative nature conservation tool which, based on thorough consideration of different implementation options of specific projects combined with public opinion research, helps eliminate solutions that fail to comply with the overriding principle of sustainable development.